Wear characteristics of multiple particle size silicon carbide reinforced aluminium composite - Abdulmumin, Adebisi Adetayo; Maleque, Md. Abdul; Ali, Mohammad Yeakub (Trans Tech Publications, Switzerland, 2015)
Metal matrix composites are attractive light weight materials with potential attributes to substitute automotive materials without sacrifing performance. This present study aims to investigate the wear characteristics of aluminium (Al) 6061 reinforced with silicon carbide particles (SiCp) of three (3) different particle sizes. The reinforcement consist of coarse particle (80μm), intermediate (40μm) and fine particles (15μm) particle sizes with 10, 5, 5 wt% respectively. The composite was fabricated using the stir casting technique due to its simplicity and cost effectiveness. The wear test was conducted using the pin on disc tribo-system with steel disc counter surface. The outcome of this study reveals that the MPS-SiC AMC exhibit better wear and frictional characteristics for brake rotor application. The coarse particles have better contribution to wear resistance because the possibility of particle pullout from the matrix for both intermediate and fine particles is high due to small surface contact area. However, the intermediate and fine particle compensates for multiple shielding effect for the base matrix thus influences the impact energy and mechanical strength of the composite. The friction coefficient (0.32 - 0.46) of the MPS-SiC AMC falls within the acceptable deviation band for automotive brake rotor application